THE HISTORY OF THE ARCHAEOLOGICAL RESEARCH OF THE BRONZE AGE SITES BY A. L. NECHITAILO - T. G. Krivtsova; L. P. Ermolenko (Гуманитарные и юридические исследования)
The article discusses the research of archaeological study of the Bronze Age sites by A. L. Nechitailo and her contribution to the research of the monuments of Maikop, North Caucasus and Ciscaucasian cultural and historical communities and cultures of the Ukrainian Steppe.